Evaluation of zinc sulfate mucoadhesive formulation on recurrent aphthous stomatitis: a randomized double-blind, placebo-controlled clinical trial - Anahita Ghorbani; Jafar Akbari; Maryam Boorboor; Zahra Nekoukar; Gohar Eslami (BMC, 2020)
Abstract Background Recurrent aphthous stomatitis (RAS) is a common lesion that affects the oral mucosa. There are several methods to treat RAS, including systemic and topical formulations. This study was conducted to evaluate the anti-inflammatory effect of topical zinc sulfate and its efficacy in the treatment of RAS. Methods A double-blind randomized clinical trial was conducted on 46 patients with RAS. They were randomly assigned into two groups to receive a zinc sulfate mucoadhesive tablet or placebo for 7 days. The pain severity was measured at baseline and daily while the diameter of the lesion was measured at baseline and on days 3, 5, and 7. The obtained data were analyzed in SPSS V.16. Results There was no significant difference in the mean diameter of lesions and pain at baseline between the two groups (P = 0.643 and P = 0.842, respectively). However, on the third, fifth, and seventh days of the study, the diameter of the lesion significantly reduced in the intervention group (P = 0.001) and the pain intensity became significantly different between groups from the fourth day of the study (P = 0.001). Conclusion Zinc sulfate mucoadhesive tablet was effective in recovery and reducing the pain and diameter of the aphthous lesion and could be considered for the treatment of RAS. Trial registration Evaluation of the effectiveness of zinc sulfate mucoadhesive tablet in the improvement of recurrent aphthous stomatitis (RAS), IRCT20151109024975N9. Registered August 1, 2018, https://en.irct.ir/trial/32423 . This project was registered by the Iranian Registry of Clinical Trials ( http://www.irct.ir ). The IRCT ID was IRCT20151109024975N9.